The impact of physical load on duration estimation in sport - Schütz, Lisa-Marie; Betsch, Tilmann; Plessner, Henning; Schweizer, Geoffrey (Psychology of sport and exercise, 2023)
We investigated whether physical load has an influence on the accuracy of duration estimation of sporting ac-tivities presented in real time and slow motion. 86 participants were studied in two single sessions of 45 min each.Our results showed no general effects for physical load, when comparing physical load versus rest. However, we could replicate findings of past research (Schutz et al., 2021), showing that the duration of sports perfor-mance is estimated more accurately when presented in real time compared to slow motion. Further we found, that under physical load, participants perceiving the physical exercise as hard (RPE >= 15) estimated time significantly shorter and more accurately compared to participants perceiving the physical exercise as light or moderate (RPE <15).Thus, our results suggest that using slow motion may worsen the assessment of sports performance. Addi-tionally, we could show that intense physical exertion contributes to reducing the overestimation of time.